Measuring European property investment performance: comparing different approaches. Issue 1 (29th April 2014) - Devaney, Steven
Abstract : Purpose: – Price indices for commercial real estate markets are difficult to construct because assets are heterogeneous, they are spatially dispersed and they are infrequently traded. Appraisal-based indices are one response to these problems, but may understate volatility or fail to capture turning points in a timely manner. This paper estimates "transaction linked indices" for major European markets to see whether these offer a different perspective on market performance. The paper aims to discuss these issues. Design/methodology/approach: – The assessed value method is used to construct the indices. This has been recently applied to commercial real estate datasets in the USA and UK. The underlying data comprise appraisals and sale prices for assets monitored by Investment Property Databank (IPD). The indices are compared to appraisal-based series for the countries concerned for Q4 2001 to Q4 2012. Findings: – Transaction linked indices show stronger growth and sharper declines over the course of the cycle, but they do not notably lead their appraisal-based counterparts. They are typically two to four times more volatile. Research limitations/implications: – Only country-level indicators can be constructed in many cases owing to low trading volumes in the period studied, and this same issue prevented sample selection bias from being analysed in depth. Originality/value: – Discussion of the utility of transaction-based price indicators is extended to European commercial real estate markets. The indicators offer alternative estimates of real estate market volatility that may be useful in asset allocation and risk modelling, including in a regulatory context.